Effects of Manure and Urea Fertilizer on Cocoa Growth (Theobroma cacao L.) - Sudarma J. A.; Masdar Hidayat (Journal of Social Science, 2022)
This research was conducted in Cingkam Mekhanggun Village, Lawe Alas District, Southeast Aceh Regency with a height of ± 250 meters above sea level. This research will be carried out from September 2020 to December 2020 with the aim of being able to determine the effect of manure and the correct dose of urea fertilizer in order to obtain the growth of cocoa plants. This study used a factorial randomized block design (RBD) consisting of 2 treatment factors and 2 replications, namely the first factor of manure (K) with treatment K1 = 100 gr / polybag, K2 = 200 gr / polybag and K3 = 300 gr / polybag. The second factor was Urea (U) fertilizer with 3 treatment levels U1 = 1 g / polybag, U2 = 2 g / polybag and U3 = 3 g / polybag, so that 9 treatment combinations were obtained. The results showed that manure could not increase the growth of cocoa seedlings, plant height, leaf area, stem diameter and biomass weight. The application of urea fertilizer cannot stimulate the growth of cocoa seedlings in the nursery. The treatment combination between manure and urea fertilizer cannot stimulate the growth of cocoa plants in the nursery